2017
DOI: 10.3390/ijms18122392
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic-Like Activity of Essential Oil Constituents: An Update

Abstract: The constituents of essential oils are widely found in foods and aromatic plants giving characteristic odor and flavor. However, pharmacological studies evidence its therapeutic potential for the treatment of several diseases and promising use as compounds with analgesic-like action. Considering that pain affects a significant part of the world population and the need for the development of new analgesics, this review reports on the current studies of essential oils’ chemical constituents with analgesic-like a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 234 publications
(294 reference statements)
0
52
0
1
Order By: Relevance
“…Compounds such as ursolic acid, rosmarinic acid, ferulic acid, caffeic acid, tanshinone IIA, and oleanolic acid, in S. miltiorrhiza could regulate pain targets. Interestingly, we also found that many of the compounds that regulate pain originate from volatile oils/essential oils molecules (de Cassia et al, 2017). Terpene compounds are the main components of volatile oils.…”
Section: Regulatory Effects Of Tcm On Related Targets Of Endometriosimentioning
confidence: 68%
“…Compounds such as ursolic acid, rosmarinic acid, ferulic acid, caffeic acid, tanshinone IIA, and oleanolic acid, in S. miltiorrhiza could regulate pain targets. Interestingly, we also found that many of the compounds that regulate pain originate from volatile oils/essential oils molecules (de Cassia et al, 2017). Terpene compounds are the main components of volatile oils.…”
Section: Regulatory Effects Of Tcm On Related Targets Of Endometriosimentioning
confidence: 68%
“…A review by de Cassia (20) reported, in particular, a significant analgesic activity of menthol in controlling acute and inflammatory pain. This could act in combination with both (-)-α-bisabolol (24), Commiphora myrrha (21), allantoin (20), anethole and licorice (27,43), which display analgesic activity together with anti-inflammatory and wound healing effects.…”
Section: Discussionmentioning
confidence: 99%
“…Tea tree (Melaleuca alternifolia), another plant belonging to this family, is characterized by antifungal (13), anti-inflammatory (14) and anti-bacterial effects (15,16). Furthermore, the extracts from the family of Lamiaceae, including Thymus vulgaris and Mentha piperita, exhibited in vitro antioxidant (17), antifungal and anti-cancer (18,19) activities, as well as analgesic effects against inflammatory pain (20). Similar effects have been reported for Commiphora myrrha (21) and Licorice (Glycyrrhiza glabra) extracts (22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essential oils are natural products that demonstrate high therapeutic potential against various types of pathologies, including central nervous system (CNS) disorders. Their chemical constituents exhibit various pharmacological activities such as anxiolytic [8], antidepressant [9], analgesic [10], anticonvulsant [11], and inhibitory effects against brain tumor cells [12]. Monoterpenes are compounds commonly found in essential oils that have received much attention as a potential therapy for AD [13].…”
Section: Introductionmentioning
confidence: 99%